Najważniejsze czynniki warunkujące stosowanie marketingu relacji przez polskie biura podróży - Dudek, Andrzej; Michalska-Dudek, Izabela (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The hereby article presents the core concept of relations marketing and survey results aimed at the assessment of relations marketing principles application in the performance of travel agencies in Poland. Following the implementation of classification trees method there were distinguished most important, for a given population, factors that determine an approach towards the problem of relations marketing application. These turned out to be the size of enterprises measured by means of the number of employed staff as well as the type of conducted business activity. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Gospodarka a Środowisko (6); 2006; nr 1145, s. 213-221